Los derechos de las personas LGTBIQ privadas de libertad en el sistema penitenciario ecuatoriano. - Marca Córdova, Bryan Paúl (2024)
ABSTRACT: The title of this iesearcli is “The rights of LGTBIQ people deprived of liberty in the Ecuadorian penitentiary system”, and has originated from the violation of the rights of LGTBIQ groups found in the Social Rehabilitation Venters of Ecuador. As such, the purpose of this investigation is to determine the deficit that exists in the penitentiary system with respect to conipliance with the rights of LGTBIQ people deprived of liberty, mainly constitutional rights such as the right to separation, the right to intimate visits, and the right to personal integrity. For cornpliance, the research was developed in two parts: first through the treatment of the constant theoretical framework in 3 units called: the first, the penitentiary system regime, the second, referring to LGTBIQ groups from the international and national perspectlve, and, the third on the violated rights of LGTBIQ groups deprived of llberty. The methodological design appropriate to a social legal investigation, through the historical-loglCál, legal-doctrinal, legal- analytical, inductive and descriptive research method; mixed research approach; types of dogmatic, descriptive legal and documentary Research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, which has made it possible to draw conclusions and recominendations according to the problem investigated.